2022
DOI: 10.3389/fpsyg.2022.1042031
|View full text |Cite
|
Sign up to set email alerts
|

On a path to becoming more self-regulated: Reflective journals’ impact on Chinese English as a foreign language students’ self-regulated writing strategy use

Abstract: A number of studies have confirmed the positive effect of writing reflective journals on L2 learning. However, the relationship between writing reflective journals and the use of self-regulated writing strategies remains unclear. To redress this knowledge gap, we assigned 38 Chinese English as a foreign language (EFL) students three journal-writing tasks in which they reflected on their writing processes and explored (1) the types of self-regulated writing strategies and changes to those strategies that the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This act of continuous self-assessment allowed her to track her progress, identify areas needing improvement, and adjust her strategies accordingly. This finding aligns with the findings of Zhang et al (2022), which emphasized the importance of reflective journaling in developing self-monitoring, self-assessment, and goal-setting among L2 students. However, in contrast to Hirose and Sasaki (2000), who found that teaching writing combined with reflective journaling enhanced only the L2 students" writing mechanics, the present study provided empirical evidence on how reflective journaling assisted students in improving all aspects of their writing, such as the structure (as in Reem"s case) and language use (as in Mona"s example).…”
Section: Monitoring Writing Progress and Refining Writing Skillssupporting
confidence: 90%
See 1 more Smart Citation
“…This act of continuous self-assessment allowed her to track her progress, identify areas needing improvement, and adjust her strategies accordingly. This finding aligns with the findings of Zhang et al (2022), which emphasized the importance of reflective journaling in developing self-monitoring, self-assessment, and goal-setting among L2 students. However, in contrast to Hirose and Sasaki (2000), who found that teaching writing combined with reflective journaling enhanced only the L2 students" writing mechanics, the present study provided empirical evidence on how reflective journaling assisted students in improving all aspects of their writing, such as the structure (as in Reem"s case) and language use (as in Mona"s example).…”
Section: Monitoring Writing Progress and Refining Writing Skillssupporting
confidence: 90%
“…Amal demonstrated how reflective journaling helped her acknowledge her strengths and identify her weaknesses. This self-awareness was crucial for effective self-monitoring, allowing her to set goals to track her progress (Cresswell, 2000;Zhang, Li, Chieh, & Han, 2022). This finding aligns with a prior study by Liao and Wong (2007), who discovered that reflective journaling provided L2 students with insights to articulate their writing strengths and identify their weaknesses to monitor their writing progress.…”
Section: Monitoring Writing Progress and Refining Writing Skillssupporting
confidence: 86%
“…Previous studies have extensively investigated the effectiveness of SRLL among Chinese college learners (e.g., Shen et al, 2023; Y. Zhang et al, 2016, 2022). These research endeavors have provided valuable insights into the factors that affect SRLL and how they influence language learning achievements within this particular context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-Regulated Language Learning Among Chinese College EFL Learners Previous studies have extensively investigated the effectiveness of SRLL among Chinese college learners (e.g., Shen et al, 2023;Y. Zhang et al, 2016Y. Zhang et al, , 2022.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation